Guanandi (Calophyllum brasiliense) clonal propagation through minicuttings - Luiz da Silva, Rogério (2009)
The goal of this research was to determine guanandi  (Calophyllum brasiliense) clonal propagation efficiency of hisforesty species through minicutting technique. A miniclonal garden was first established in sand beds, where new sprouts were produced for their use as minicuttings. Two experiments were performed in order to refine propagation protocols. The first experiment assessed the performance of 2 different types of minicuttings (apical and intermediate within the sprout) exposed to three IBA dosages (0, 2000, 4000, and 8000 mg.l-1). In the second experiment, minicuttings were sown in 3 different substrates (vermiculite, burned rice husk and decomposed pine-bark). Rooting percentages did not vary among treatments in the first experiment. In the second experiment, a greenhouse permanency time reduction, under vermiculite substrate condition, was registered. As a general conclusion, the minicutting technique was an efficient strategy for guanandi clonal propagation.